(untitled) (Voice: A Biannual & Bilingual Journal, 2025)
Through an empirical approach, this paper critically rethinks the reasons behind the increased capital requirements imposed on Nepalese banks that apply the Basel III framework. The paper will be designed based on interviews with banking professionals and their regulatory officials to provide a critical view of inadequate risk management practices, concerns over financial stability, deficiencies in supervisory oversight, and challenges in corporate governance in Nepal’s banking industry. The results indicate that Nepal Rastra Bank has implemented elevated capital standards as a cautious risk management strategy, customized to the country’s specific economic context, to enhance the resilience of banks against systemic risks and mitigate financial threats. The study aims to cover sectors such as risk management and supervisory frameworks, emphasizing the need for continuous reforms to scale up risk assessment, transparency, and internal control systems. These are key alignments for Nepal’s banking sector to meet global standards, promoting sustainable economic development.